2012
DOI: 10.1111/j.1532-950x.2011.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after Renal Transplantation in 26 Dogs

Abstract: Canine renal transplantation in clinical patients is associated with a high morbidity and mortality and increasing recipient age has a negative association with outcome. Thromboembolic complications are a major cause of death in the immediate postoperative period and effective anticoagulation protocols may greatly improve survival in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 50 publications
0
37
0
1
Order By: Relevance
“…They are also used to prevent organ rejection after transplantation and to reduce immunological reactions associated with some infectious diseases, such as feline infectious peritonitis (FIP) and ehrlichiosis (Cohn, 2003;Gregory et al, 2006;Case et al, 2007;Addie et al, 2009;Hopper et al, 2012). They are also used to prevent organ rejection after transplantation and to reduce immunological reactions associated with some infectious diseases, such as feline infectious peritonitis (FIP) and ehrlichiosis (Cohn, 2003;Gregory et al, 2006;Case et al, 2007;Addie et al, 2009;Hopper et al, 2012).…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…They are also used to prevent organ rejection after transplantation and to reduce immunological reactions associated with some infectious diseases, such as feline infectious peritonitis (FIP) and ehrlichiosis (Cohn, 2003;Gregory et al, 2006;Case et al, 2007;Addie et al, 2009;Hopper et al, 2012). They are also used to prevent organ rejection after transplantation and to reduce immunological reactions associated with some infectious diseases, such as feline infectious peritonitis (FIP) and ehrlichiosis (Cohn, 2003;Gregory et al, 2006;Case et al, 2007;Addie et al, 2009;Hopper et al, 2012).…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…In dogs, CLM can be used as one of the therapeutic options for the treatment of severe or refractory leproid granuloma [14]. In canine kidney transplant patients, the occurrence of bacterial infections, such as upper respiratory tract infections and pneumonia, as a post-operative complication due to long term immunosuppression has been reported [5, 7, 17]. Hopper et al reported that bacterial infections were considered as the cause of death in 23% of canine kidney transplant patients [7].…”
mentioning
confidence: 99%
“…In canine kidney transplant patients, the occurrence of bacterial infections, such as upper respiratory tract infections and pneumonia, as a post-operative complication due to long term immunosuppression has been reported [5, 7, 17]. Hopper et al reported that bacterial infections were considered as the cause of death in 23% of canine kidney transplant patients [7]. In healthy beagles, 10 mg/kg PO of CLM produced serum concentrations of approximately 3 µ g/m l , although steady-state studies have not been performed in dogs [20].…”
mentioning
confidence: 99%
“…Previous reports in humans have suggested that significantly reducing immunosuppressant doses are extremely important to treat bacterial pneumonia in kidney transplant recipients [19]. Unlike human and feline renal transplant patients, canine recipients require highly aggressive immunosuppressive therapy, because of the intense host response these animals mount against the graft [9]. A previous veterinary report has shown that the death of canine patients can occur due to graft rejection when immunosuppressive drug doses are decreased to control infectious pneumonia [11].…”
mentioning
confidence: 99%
“…Most of these studies have focused on the effectiveness of immunosuppression protocols, surgical techniques and the survival of the animal recipients [4, 9, 17]. Although some reports have briefly described successful recovery from bacterial complications that were not due to MDR strains, others have presented cases in which the infections did not respond well to treatment with antimicrobials [9, 11]. Infection with multidrug-resistant (MDR) Pseudomonas (P.) aeruginosa in kidney transplant recipients leads to life-threatening complication in humans [16].…”
mentioning
confidence: 99%